Rethinking the Role and Architectural Value of the St. Andrew Kim Dae-Geon Memorial Church in the Mirinae Shrine in Korea - Seo, Myengsoo (Religions, 2021)
This paper reconsiders the role and value of the St. Andrew Kim Dae-Geon Memorial Church and his grave site in the Mirinae Shrine, currently recognized as a special place of pilgrimage for Catholics in Korea. The Mirinae area is the place where the remains of Father Kim Dae-Geon were relocated after his martyrdom in 1846. To commemorate this, the St. Andrew Kim Dae-Geon Memorial Church was built in 1928 by his grave, and his relics and image are enshrined within. This research examines the value of the church and his grave site from three perspectives: first, the historical value related to Father Kim Dae-Geon; second, the architectural value of the Memorial Church; and third, value from the sense of place (or genius loci) of the church and environs. The role and architectural value of the building and site were examined through a literature review, an archival investigation, and a visit to the site. This research is about interpretation of the church and Father Kim Dae-Geon’s grave site in the Mirinae Shrine—not only the building itself, but also its sense of place, beyond the historical research focusing on the person.